The evolution and internalization of international joint ventures in a transitioning economy - Steensma, H Kevin; Barden, Jeffrey Q; Dhanaraj, Charles; Lyles, Marjorie; Tihanyi, Laszlo (Journal of International Business Studies, 2008)
Although international joint ventures (IJVs) may mature over time and develop competitive viability, they maintain some risk of instability owing to their shared ownership. Such instability can ultimately lead to their internalization by one of the partners. In this study, we consider factors that influence (1) whether IJVs evolve toward becoming a wholly owned subsidiary, and (2) which parent (foreign or local) gains ownership of the venture. We use a sample of Hungarian joint ventures, and find that only when there is both a power imbalance between the parents and high levels of conflict is the likelihood that the joint venture converts to a wholly owned subsidiary enhanced. The extent to which the joint venture has learned from the foreign parent indirectly determines which parent gains full ownership. Extensive knowledge transfer to a joint venture in a transitioning economy combined with high levels of conflict increases the likelihood of the foreign parent gaining full ownership. In contrast, when there is extensive knowledge transfer and low conflict between the parents, the local parent is more likely to internalize the venture. Our results suggest that the relationship between partner power and outcomes in ventures is more complex than originally believed, and is contingent upon the level of conflict between the parents of the IJV.